Utility of early transperineal template‐guided prostate biopsy for risk stratification in men undergoing active surveillance for prostate cancer. (17th January 2018) - Voss, James; Pal, Raj; Ahmed, Shaista; Hannah, Magnus; Jaulim, Adil; Walton, Thomas
Abstract : Objective: To assess the accuracy and utility of routine multiparametric magnetic resonance imaging (mpMRI) and transperineal template‐guided prostate biopsy (TPB) after enrolment in active surveillance (AS). Patients and Methods: From April 2012 to December 2016 consecutive men from our single institution, diagnosed with low‐ or intermediate‐risk prostate cancer on transrectal ultrasonography‐guided biopsy, were offered further staging with early mpMRI and TPB within 12 months of diagnosis. Data were collected prospectively. Eligibility criteria comprised: age ≤77 years; Gleason score ≤3 + 4; clinical stage T1–T2; PSA ≤15 ng/mL; and <50% positive biopsy cores. Results: A total of 208 men were enrolled, including 196 with Gleason score 3 + 3 and 12 with Gleason score 3 + 4 disease. The median (range) number of TPB cores was 50 (17–161), with a mean TPB core density of 1.2 cores/cm 3 prostate volume. A total of 83 men (39.9%) underwent histopathological upgrading after TPB, including 76 men (38.8%) with Gleason score 3 + 3 disease and seven men (58.3%) with Gleason score 3 + 4 disease. Of these, 26 (31.3%) were found to harbour primary pattern Gleason grade ≥4 disease. In all, 24 (28.9%) upgraded cases had Prostate Imaging Reporting and Data System (PI‐RADS) score 1 or 2 lesions on mpMRI, including five men with Gleason score ≥4 + 3 disease. Of these, 14 (58.3%) had a prostate‐specific antigen (PSA) density of ≥0.15, including four out of the five men with Gleason ≥4 + 3 disease. Overall there was a change in prostate cancer management in 77 men (37.0%) after TPB. Conclusions: Early TPB during AS is associated with significant upgrading and a change in treatment plan in over a third of men. If TPB was omitted in men with a PI‐RADS score <3 and a PSA density <0.15, 12% of those harbouring more significant disease would have been misclassified.